Asymmetry of Characteristics of the Right—Left Hemodynamic Balance of Microcirculation in the Temporal Skin Areas of the Head in Young Male and Female Subjects - Mezentseva, L. V. (Bulletin of experimental biology and medicine, 2023)
The indices of asymmetry of microcirculation in the skin of the temporal areas of the head in young male and female subjects were studied. In 20 healthy volunteers (10 men and 10 women, age 18-19 years), synchronous measurements of the microcirculation of the skin of the symmetrical temporal areas of the head were carried out by laser Doppler flowmetry. The coefficients of asymmetry of regression relationships between perfusion changes in each side and initial perfusion values in both the same and opposite sides, the distribution function of perfusion asymmetry coefficients, and variability of perfusion in the studied areas were analyzed. The sex differences of the measured characteristics of asymmetry were revealed. In men, the distribution functions of perfusion asymmetry are pointed, with positive excesses, and in women they were flat, with negative excesses. In female subjects, the contribution of the right microcirculatory bed to the right—left hemodynamic balance was higher. These findings support the hypothesis on greater plasticity of the female brain in comparison with the male brain.